Perencanaan Kurikulum Pendidikan Agama Islam Madrasah Ibtidaiyah Swasta Al-Ikhlas Kampung Dalam Kecamatan Bilah Hulu Kabupaten Labuhanbatu - Usiono, Usiono; Syafaruddin, Syafaruddin; Fuadi, Wirdatul (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
This study aims to find out how the planning of the Islamic Religious Education curriculum at MIS Al-Ikhlas Kampung Dalam District of Bilah Hulu, Labuhanbatu Regency. This research was conducted using qualitative descriptive. Where this descriptive data is carried out by describing, using and describing events that researchers get in the field related to Islamic Religious Education Curriculum Planning. The findings of this study are: first, planning the Islamic Religious Education curriculum begins with an evaluation of the curriculum used in the previous year. The results of the evaluation will be used as consideration for the preparation of the next curriculum. Second, Some of the supporting and inhibiting factors in planning the Islamic Religious Education curriculum, Meanwhile, the inhibiting factors in planning the Islamic education curriculum are educators who have less experience, inadequate facilities and infrastructure, and low costs. Third, The strategy in overcoming the Inhibiting Factors of Planning Islamic Religious Education Curriculum to overcome the problem of teachers who have difficulty developing curriculum planning, madrasas send these teachers to attend trainings, strategies to overcome the problem of facilities and infrastructure, madrasas carry out moving classes, classes are used as libraries, prayer rooms but not completely, while in overcoming funding problems for madrasah principals.